Effects of global warming on plateau plants (Bangladesh Journal of Botany, 2021)
Biological and ecological environment in the plateau climate warming, abiotic environmental factors to different degrees of change were summed up from the macroscopic level to microcosmic individual physiological level of global climate change response model. The study summarized the research achievements at home and abroad, pointed out the plant phenology, photosynthesis, nutrient structure and presents different response patterns. These different response modes, from micro to macro, will eventually lead to changes in the structure and function of the Plateau ecosystem. This will threaten the survival and development of the Plateau plants on a large scale. Finally, the future research emphases in this field would be prospected.Bangladesh J. Bot. 50(3): 963-968, 2021 (September) Special